PENGAMBILAN KEPUTUSAN YANG EFEKTIF DALAM MANAJEMEN BERBASIS SEKOLAH (MBS) - Ketut Bali Sastrawam (Purwadita : Jurnal Agama dan Budaya, 2019)
School-based management is inseparable from the performance of education in a countrybased on the existing education system. School-Based Management (SBM) is the process ofintegrating, coordinating and utilizing it by involving thoroughly the elements that exist in theschool as well as the cooperation between the school, the community, and the government withtheir respective responsibilities, to achieve the objectives (quality of education) that expectedefficiently. The rational decision-making model goes through six steps, namely (1) determiningthe problem, (2) identifying decision criteria, (3) allocating bobo on criteria, (4) developingalternatives, (5) evaluating alternatives, and (6) having the best alternatives. In order for decisionstaken within the framework of the MBS to produce maximal results, decision making must berealized in the presence of as complete information as possible.